INTERPRETASI TEKANAN AIR PORI SEBAGAI DASAR PEMELIHARAAN PIEZOMETER DI BENDUNGAN SERMO - Faris Setiawan; Ignatius Sriyana (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2022)
Pore water pressure readings (piezometer readings) produce data that must be interpreted before being used for further analysis. This process is very influential on the results of the analysis because in the piezometer reading there is the possibility of anomalies due to potential delays or lags or errors in readings. The purpose and objective of this research is to provide an alternative approach to dam safety instrumentation inventory in order to be able to arrange maintenance work properly, effective and efficient, in conditions of limited budget can be used as a standard in making decisions in prioritizing piezometer maintenance. Several piezometer data processing methods can use techniques, including : interpretation of pore water pressure patterns; correlation simulation of pore pressure values and flow line plots. The results of the research on the piezometer at the Sermo Dam can be distinguished between conditions that have good pore water pressure readings and the opposite condition, with a ratio of 71,43% and 28,57%.